Features of Preoperative Preparation of Patients with Burns and Chronic Ulcers of Various Etiology for Autodermoplasty - M. V. Varganov; A. A. Miklichev; K. D. Bogdanov (Антибиотики и Химиотерапия, 2021)
The influence of various schemes of preoperative preparation for autodermoplasty on the rates of skin graft survival and the duration of hospitalization in patients with burns and wounds of various etiologies was analyzed. Patients were divided into groups and subgroups depending on the preparation scheme. Group I (22 patients) received negative pressure wound therapy (NPWT) during the preoperative period for 5 days in combination with reamberin — intravenous drip at a rate of 40-60 drops/min, 500 ml, once a day for 5 days. Those patients were divided into subgroups: subgroup 1A (17 people) received complex treatment without antibiotic therapy, subgroup 1B (5 people) received antibiotic therapy. Group II consisted of 30 patients, who received vacuum therapy during the preparatory period. Group II patients were also divided into subgroups: 2A (16 people) received NPWT without antibiotics, 2B (14 people) — vacuum therapy together with antibiotic therapy. Group III (comparison, n=52) included patients who were treated using traditional methods, including antibiotic therapy and topical use of various dressings and ointments. Follow-up morphohistological study of wound biopsies was carried out in order to determine the area of fibroblasts, the area of fibroblast nucleus, and the number of vessels. After skin autografting, skin flap survival rate was determined, taking the time of hospitalization into account. Upon comparison of preoperative preparation schemes used for patients with burns and chronic ulcers of various etiologies with a surface area of 1–5% appropriate for skin autografting, the scheme that included NPWT and reamberin for 5 days proved to be the most effective: an improvement in fibroblastogenesis and blood flow to the wound was noted in this group of patients, which was accompanied by an improvement in the skin flap survival rate up to 90.0±9.9%, which, in turn, reduced the duration of patient’s hospital stay — the average duration of the preoperative period was 2.5 times shorter, postoperative — 1.9 times shorter than in the comparison group (p<0.05). The results obtained make it possible to recommend the use of this scheme in the preoperative preparation for skin autografting for patients with burns and chronic ulcers of various etiologies with the surface area of 1–5%.